2014
DOI: 10.1186/1472-6874-14-74
|View full text |Cite
|
Sign up to set email alerts
|

Barriers among Danish women and general practitioners to raising the issue of intimate partner violence in general practice: a qualitative study

Abstract: BackgroundThirty-five percent of Danish women experience sexual or physical violence in their lifetime. However, health care professionals are not in the practice of asking about intimate partner violence (IPV) in Denmark. It is currently unknown what hinders general practitioners from asking about partner violence and how Danish women would perceive such an inquiry. This aspect has not previously been explored in Denmark. An exploratory study was conducted to examine what hinders general practitioners (GPs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…These include women's experiences of violence (Almqvist & Broberg, ; Bergman, ; Bruno, ; Enander, , , , ; Eriksson & Ulmestig, ; Flinck, Paavilainen, & Astedt‐Kurki, ; Häggblom & Möller, ; Hydén, , , ; Jarnkvist & Brännström, ; Römpötti, ; Scheffer Lindgren & Renck, ), of violence during pregnancy (Edin, Dahlgren, Lalos, & Högberg, ; Edin & Högberg, ; Edin & Nilsson, ; Engnes & Lundgren, ; Finnbogadóttir, Dykes, & Wann‐Hansson, ) and motherhood (Almqvist & Broberg, ; Georgsson et al, ), and of leaving violent relationships (Enander, ; Enander & Holmberg, ; Häggblom & Möller, ; Holmberg & Enander, ; Hydén, , ; Hydén, ; Jarnkvist, ; Münger, ; Scheffer Lindgren & Renck, ). Studies have investigated women's experiences with the judicial (Agevall, ; BRÅ, ; Brännvall, ; Bruno, ; Ekström, ; Green, ; Jarnkvist, ; Jarnkvist & Brännström, ), social service (Eriksson & Ulmestig, ; Jarnkvist & Brännström, ; Nikupeteri, ; Ulmestig & Panican, ) and health care systems (Garnweidner‐Holme, Lukasse, Solheim, & Henriksen, ; Gillå et al, ; Häggblom & Möller, ; Leppakoski, Paavilainen, & Astedt‐Kurki, ; Mørk, Andersen, & Taket, ; Örmon & Hörberg, ; Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Pratt‐Eriksson, Bergbom, & Lyckhage, ). The impact of IPVAW on the health (Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Scheffer Lindgren & Renck, ), economy (Eriksson & Ulm...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include women's experiences of violence (Almqvist & Broberg, ; Bergman, ; Bruno, ; Enander, , , , ; Eriksson & Ulmestig, ; Flinck, Paavilainen, & Astedt‐Kurki, ; Häggblom & Möller, ; Hydén, , , ; Jarnkvist & Brännström, ; Römpötti, ; Scheffer Lindgren & Renck, ), of violence during pregnancy (Edin, Dahlgren, Lalos, & Högberg, ; Edin & Högberg, ; Edin & Nilsson, ; Engnes & Lundgren, ; Finnbogadóttir, Dykes, & Wann‐Hansson, ) and motherhood (Almqvist & Broberg, ; Georgsson et al, ), and of leaving violent relationships (Enander, ; Enander & Holmberg, ; Häggblom & Möller, ; Holmberg & Enander, ; Hydén, , ; Hydén, ; Jarnkvist, ; Münger, ; Scheffer Lindgren & Renck, ). Studies have investigated women's experiences with the judicial (Agevall, ; BRÅ, ; Brännvall, ; Bruno, ; Ekström, ; Green, ; Jarnkvist, ; Jarnkvist & Brännström, ), social service (Eriksson & Ulmestig, ; Jarnkvist & Brännström, ; Nikupeteri, ; Ulmestig & Panican, ) and health care systems (Garnweidner‐Holme, Lukasse, Solheim, & Henriksen, ; Gillå et al, ; Häggblom & Möller, ; Leppakoski, Paavilainen, & Astedt‐Kurki, ; Mørk, Andersen, & Taket, ; Örmon & Hörberg, ; Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Pratt‐Eriksson, Bergbom, & Lyckhage, ). The impact of IPVAW on the health (Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Scheffer Lindgren & Renck, ), economy (Eriksson & Ulm...…”
Section: Methodsmentioning
confidence: 99%
“…Experiences and discourses of professionals working with the social services (Edin, Högberg, Dahlgren, & Lalos, 2009;Edin, Lalos, Högberg, & Dahlgren, 2008;Ekström, 2017Ekström, , 2018Helmersson, 2017;Keskinen, 2005;Kullberg, Skillmark, Nord, Pers, & Fäldt, 2015;Mattson, 2011Mattson, , 2013, police (Åkerström, 1998;BRÅ, 2000;Eriksson, 1995;Lundberg, 2001;Weinehall, 2011), prosecution service (Eriksson, 1995;Törnqvist, 2017;Weinehall, 2011), and health care (Finnbogadottir & Dykes, 2012;Gillå et al, 2018;Häggblom & Möller, 2008;Henriksen, Garnweidner-Holme, Thorsteinsen, & Lukasse, 2017;Hultmann, Möller, Ormhaug, & Broberg, 2014;Husso et al, 2012;Mørk et al, 2014;Socialstyrelsen, 2002;Stenson, Sidenvall, & Heimer, 2005;Sundborg, Törnkvist, Saleh-Stattin, Wändell, & Hylander, 2015) have been researched, as has the experience of teachers (Bruno, 2012) encountering violence against mothers. The perceptions of local-level decision makers and professionals on gender equality (Holmberg & Bender, 2003) and IPVAW prevention (Hensing, Von Borgenstede, Jakobsson, Krantz, & Spak, 2008;Jakobsson, von Borgstede, Krantz, & Hensing, 2013) have also been explored.…”
Section: Included Studies and Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Joyner and Mash (2014) reported that judgemental or directive counselling, based in beliefs that abused women were not active participants in their own health, was detrimental to providerpatient relationships and overall care. Women with and without experiences of IPV interviewed by Mork, Andersen, and Taket (2014) discussed the importance of respectful communication from providers. Further, an interview study with cancer survivors who had experienced CSA indicated that survivors wanted providers to address imbalanced power dynamics (Gesink & Nattel, 2015).…”
Section: Provider-patient Relationshipmentioning
confidence: 99%
“…Sundborg, Tornkvist, Saleh‐Stattin, Wandell, and Hylander () suggested that the factors that facilitate nurses asking questions of women exposed to violence are having strategies for asking, knowing how to deal with the answers, and having a supportive environment (Sundborg et al., ). When asking about gender‐based violence, questions should be posed in an empathic, sensitive and nonjudgemental way (McCormack, Dewing, & McCance, ; Mørk, Andersen, & Taket, ).…”
Section: Discussionmentioning
confidence: 99%